Effects of Anthropogenic Activities on Pore Pressure of the Earth’s Crust - A Desk Review - Naeem, Zainab (Journal of Development Policy Research and Practice (JoDPRP), 2017)
The objective of this chapter is to identify and analyse the major anthropogenic factors affecting pore pressure of the rocks inside the Earth’s crust which determines the frequency of earthquakes and is responsible for causing seismic events, eventually leading to seismic movements. These activities include construction of dams, hydraulic fracking, carbon sequestration, and radiations from certain technologies such as the United States’ High Frequency Active Auroral Research Program (HAARP) which is now being used for research purposes. It also studies how temperature and pressure are related and trigger earthquakes and how global warming is affecting the Earth’s pore pressure. The effects of these factors were assessed on different parts of the world such as in the USA, Pakistan and India, where earthquakes were triggered. The study is based on desk research, including review of research papers and case studies on the subject. The findings from this secondary review indicated that fracking and building reservoirs have resulted in significant seismic events in many parts of the world, even in areas such as Oklahoma, USA, which were not seismically active, but which witnessed earthquakes after fracking and reservoir projects were initiated (Rubinstein and Mahani 2015). Moreover, there exists a positive correlation between temperature increase and earthquake frequency (Usman et al. 2016). Furthermore, the chapter also studies if the radiations emitted under programmes such as HAARP can cause disturbance in the earth’s crust because very low frequency radiations emitted from transmitters towards ionosphere, gets reflected back to the earth, can also trigger seismic movements in the crust (Kim et al. 2002). However, human factors such as building of artificial dams, and hydraulic fracking are also major contributing factors towards increasing the frequency of earthquakes around the globe (Petersen et al. 2016). The chapter discusses how the Sendai Framework can play a role to reduce the impacts of anthropogenic activities which can trigger disasters, such as earthquakes. The scope of this article is related to the following SDG / SDGs.